Blue-phase liquid crystal elastomer with high thermal stability as well as preparation method and application of blue-phase liquid crystal elastomer

By introducing aromatic thiol monomers into the blue-phase liquid crystal elastomer to extend the polymer chain, the problem of insufficient thermal stability of the blue-phase liquid crystal elastomer in the prior art is solved, and high thermal stability, excellent optical properties and mechanical ductility are achieved.

CN119859533APending Publication Date: 2025-04-22TECHNICAL INST OF PHYSICS & CHEMISTRY - CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311365232.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-20
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

While improving the elastic properties of existing blue-phase liquid crystal elastomers, the thermal stability is difficult to improve, resulting in limited application in high-temperature environments.

Method used

By introducing aromatic thiol monomers into the blue phase liquid crystal elastomer as a chain extender and chain transfer agent, the polymer chain is extended, elasticity is increased, and the mechanical ductility and thermal stability are improved by regulating the content and treatment conditions of each component.

Benefits of technology

The high thermal stability of the blue-phase liquid crystal elastomer is achieved, the application temperature domain is expanded, and excellent optical properties and mechanical ductility are maintained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859533A_ABST
    Figure CN119859533A_ABST
Patent Text Reader

Abstract

The invention discloses a blue-phase liquid crystal elastomer with high thermal stability and a preparation method and application thereof. In the blue-phase liquid crystal elastomer with high thermal stability, raw materials for preparing the blue-phase liquid crystal elastomer comprise nematic-phase liquid crystal, a liquid crystal polymerizable monomer, a chiral compound, a photoinitiator and a thiol monomer, wherein the thiol monomer is an aromatic thiol monomer. The blue-phase liquid crystal elastomer has excellent optical quality, good mechanical ductility and high thermal stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of blue phase liquid crystal materials, and more specifically to a blue phase liquid crystal elastomer with high thermal stability, a preparation method thereof and an application thereof. Background Art

[0002] The blue phase of liquid crystal is a special phase that exists between the isotropic state and the cholesteric phase, mainly composed of a double twisted helical structure and defects in between. Due to the existence of defects, the stable existence range of blue phase liquid crystal is very narrow, usually only one to two degrees. In order to solve the narrow temperature range of the blue phase and improve thermal stability, scholars have proposed a variety of methods. The most commonly used and simple method is the polymer stabilization method. This method can stabilize the defects of the double twisted double helical structure by forming a polymer network, thereby enhancing thermal stability. However, due to the strong rigidity of the polymer skeleton, the blue phase liquid crystal has poor tensile properties, making it difficult to achieve simple mechanical color change, and the thermal reversibility is poor.

[0003] Blue phase liquid crystal elastomer is a new type of stimulus-responsive material that combines three-dimensional structural color with the rubber elasticity of the elastomer network. By adding chain extenders or using chain polymer monomers to reduce the network density of the polymer network, the elasticity of the polymer network is increased, and the lattice structure of the blue phase liquid crystal is fixed. By introducing thiol monomers into blue phase liquid crystal elastomers, its overall elastic properties can be improved, but current research has found that while significantly improving the elastic properties, it is difficult to improve thermal stability. Summary of the invention

[0004] Based on the above facts, the purpose of the present invention is to provide a blue phase liquid crystal elastomer with high thermal stability and a preparation method and application thereof. The blue phase liquid crystal elastomer has excellent optical quality, good mechanical ductility and high thermal stability.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] In one aspect, the present invention provides a blue phase liquid crystal elastomer with high thermal stability, wherein the raw materials for preparing the blue phase liquid crystal elastomer include:

[0007] Nematic liquid crystals, liquid crystal polymerizable monomers, chiral compounds, photoinitiators and thiol monomers;

[0008] Wherein, the thiol monomer is an aromatic thiol monomer.

[0009] Aromatic thiol monomers react as chain extenders and chain transfer agents. By adding aromatic thiol monomers, the polymer chain can be extended and the elasticity of the blue phase liquid crystal polymer can be increased. On the basis of ensuring that the elastomer has good optical properties, the mechanical ductility and thermal stability of the elastomer can be improved.

[0010] Furthermore, the structural formula of the thiol monomer is as shown below:

[0011]

[0012] This polymer not only increases the elasticity of the blue phase liquid crystal polymer, but also has no liquid crystal properties and will fill in the BP lattice defects to stabilize the defects.

[0013] Furthermore, in terms of mass percentage, the content of the thiol monomer in the raw material is 3-10wt%. Exemplarily, the content of the thiol monomer includes but is not limited to 4-7wt%, 5-7wt%, 6-7wt%, 4-5wt%, 4-6wt%, 4.56wt%, 5.32wt%, 6.08wt%, 6.84wt%, etc. The elastomer obtained at this time can improve the mechanical ductility and thermal stability of the elastomer while ensuring that the elastomer has good optical properties.

[0014] By controlling the amount of thiol monomer added, the temperature at which BP appears and the soft elasticity of the sample can be changed, thereby better adjusting the thermal stability of the obtained elastomer.

[0015] Furthermore, the nematic liquid crystal is selected from one or more of HTG135200-100 and E7.

[0016] Furthermore, in terms of mass percentage, the content of nematic liquid crystal in the raw material is 20-80wt%. Exemplarily, the content of nematic liquid crystal includes but is not limited to 50-70wt%, 55-70wt%, 60-70wt%, 50-65wt%, 55-65wt%, 55-60wt%, etc. The obtained elastomer can improve the mechanical ductility and thermal stability of the elastomer while ensuring that the elastomer has good optical properties.

[0017] Furthermore, the liquid crystal polymerizable monomer is selected from one or more of C6M, C3M, RM257 and C11A.

[0018] Furthermore, in terms of mass percentage, the content of the liquid crystal polymerizable monomer in the raw material is 10-70wt%. Exemplarily, the content of the liquid crystal polymerizable monomer includes but is not limited to 10-40wt%, 10-30wt%, 20-30wt%, 30wt%, etc. The obtained elastomer can improve the mechanical ductility and thermal stability of the elastomer while ensuring that the elastomer has good optical properties.

[0019] Furthermore, the chiral compound is selected from one or more of R5011, S5011 and LC756. The Bragg reflection peak of the liquid crystal elastomer is related to the chiral compound. In some preferred implementation cases, R5011 with right-handed helical properties is used to adjust the helical pitch of the blue phase liquid crystal.

[0020] Further, in terms of mass percentage, the content of the chiral compound in the raw material is 2.5-4wt%. Exemplarily, the content of the chiral compound includes but is not limited to 2.5-3.5wt%, 2.5-3wt%, 3-3.5wt%, 3-4wt%, 2.75wt%, 3.3wt%, 3.4wt%, 3.7wt%, etc.

[0021] Furthermore, the photoinitiator is selected from one of I-651, I-819, I-2959 and I-184.

[0022] Furthermore, in terms of mass percentage, the content of the photoinitiator in the raw material is 0.2-4wt%. Exemplarily, the content of the chiral compound includes but is not limited to 0.2-4wt%, 0.2-2wt%, 0.2-1wt%, 0.5-2wt%, 0.5-1wt%, 1wt%, etc.

[0023] Furthermore, in the raw materials for preparing the blue phase liquid crystal elastomer, the nematic phase liquid crystal is selected from HTG135200-100 (clearing point T c =96.3°C), the liquid crystal polymerizable monomer is selected from C6M, the thiol monomer is selected from The chiral compound R5011 and the photoinitiator are selected from I-651. The elastomer prepared under this condition has better mechanical ductility and thermal stability.

[0024] It should be noted that the mass percentage of each component (nematic liquid crystal, liquid crystalline polymerizable monomer, chiral compound, photoinitiator, thiol monomer) mentioned in the technical solution of the present invention is relative to the total amount of nematic liquid crystal, liquid crystalline polymerizable monomer, chiral compound, photoinitiator and thiol monomer.

[0025] In another aspect, the present invention provides a method for preparing the blue phase liquid crystal elastomer as described above, the preparation method comprising the following steps:

[0026] After mixing the nematic liquid crystal, the liquid crystal polymerizable monomer, the chiral compound and the photoinitiator, the thiol monomer is added and mixed to obtain a mixture;

[0027] After heating the mixture to a clear point of liquid crystal, pouring it into a liquid crystal box;

[0028] After cooling to BPⅠ, the mixture is polymerized by ultraviolet light to obtain the blue phase liquid crystal elastomer.

[0029] In some examples, the method for mixing nematic liquid crystal, liquid crystal polymerizable monomer, chiral compound and photoinitiator can be first adding a solvent to the mixture of nematic liquid crystal, liquid crystal polymerizable monomer, chiral compound and photoinitiator to completely dissolve the liquid crystal molecules, and then vacuum drying and stirring the mixture to remove the solvent.

[0030] Furthermore, the cooling is programmed cooling.

[0031] Furthermore, the cooling method is:

[0032] Cool down to BPⅡ at a rate of 0.1-5℃ / min and keep warm under this condition;

[0033] Then cool down to BPI at a rate of 0.01-0.1℃ / min and keep warm under this condition.

[0034] Furthermore, the cooling method is:

[0035] Cool down to BPⅡ at a rate of 0.1-5℃ / min and keep at this condition for 60min;

[0036] Then cool down to BPI at a rate of 0.01-0.1℃ / min and keep at this condition for 120min.

[0037] Furthermore, the conditions for the ultraviolet light polymerization are:

[0038] The wavelength of the ultraviolet light is 365nm and the light intensity is 50mW / cm 2 , the lighting time is 60-300s.

[0039] In another aspect, the present invention provides the use of the blue phase liquid crystal elastomer as described above in the preparation of stimulus-responsive three-dimensional soft photonic crystal structure materials and sensing, display and anti-counterfeiting devices.

[0040] The beneficial effects of the present invention are as follows:

[0041] In the technical solution of the present invention, a blue phase liquid crystal elastomer with high thermal stability is obtained by selecting a blue phase liquid crystal system, using a special thiol monomer, and regulating the content of each component. The advantage of the technology of the present invention is that the blue phase liquid crystal system is relatively stable, the prepared blue phase liquid crystal elastomer has excellent optical quality and a wide blue phase temperature range, and by adjusting and controlling the introduced thiol content, the temperature range in which the reflectivity of the elastomer is maintained at more than 20% can be increased from 30-150°C to 3-190°C. Finally, an elastomer with thermal reversibility and high thermal stability is obtained, the reflectivity of the elastomer remains basically unchanged within the range of 150°C (-60°C to 90°C), and the sample remains intact and undamaged when it exceeds 220°C. As an elastomer, the sample's tensile color change range covers the entire visible light band. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] The specific implementation modes of the present invention will be further described in detail below in conjunction with the accompanying drawings.

[0043] Figure 1 The preparation process of the blue phase liquid crystal elastomer is shown.

[0044] Figure 2 POM photographs and reflection spectra of the blue phase liquid crystal elastomers before and after polymerization in Examples 1, 2, and 3 are shown.

[0045] Figure 3 a, b) POM photos of the blue phase liquid crystal elastomer before and after polymerization, c) reflection spectrum, d) Koseel picture after polymerization, and e) actual photos of the stretching process in Example 2 are shown.

[0046] Figure 4 The thermal stability of the blue phase liquid crystal elastomer in Example 4 is shown, including a POM photograph of the temperature rising from -60°C, and a curve showing the dependence of wavelength and reflectivity on temperature.

[0047] Figure 5 The thermal reversibility of the blue phase liquid crystal elastomer in Example 4 is shown, including POM photographs and reflection spectra when the temperature is increased from room temperature to 150° C. and then decreased.

[0048] Figure 6 The thermal stability of the blue phase liquid crystal elastomer in Examples 4, 5, 6, and 7 is shown, including POM photographs of the temperature increase process from 30°C to 200°C and the dependence of the Bragg reflection peak on temperature. DETAILED DESCRIPTION

[0049] In order to more clearly illustrate the present invention, the present invention is further described below in conjunction with preferred embodiments and accompanying drawings. Similar components in the accompanying drawings are represented by the same reference numerals. It should be understood by those skilled in the art that the content specifically described below is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.

[0050] Example 1

[0051] A method for preparing a blue phase liquid crystal elastomer with high thermal stability comprises the following steps:

[0052] 1) Weigh 60.17%, 30%, 2.75%, and 1% of nematic liquid crystal HTG135200-100, liquid crystal polymerizable monomer C6M, chiral compound R5011 with right-handed helical properties, and photoinitiator benzoin dimethyl ether (I-651) according to mass percentage, put them into a 5mL sample bottle, add appropriate amount of dichloromethane to completely dissolve the liquid crystal molecules. Then put the sample bottle into a vacuum drying oven at 40°C overnight to allow the dichloromethane to completely evaporate, and finally obtain a fully and evenly mixed liquid crystal precursor;

[0053] 2) Heat the sample on a hot plate to above the clearing point and use magnetic stirring for more than 30 minutes to ensure that the sample is fully mixed;

[0054] 3) Add 3 μL of catalyst DPA and 6.08% by mass of thiol monomer BDMT at room temperature, and stir magnetically for more than 10 minutes to ensure that the newly added sample is evenly dispersed;

[0055] 4) Preparation of liquid crystal box: After the glass slide was ultrasonically treated with detergent for 30 minutes, rinsed with tap water for 15 minutes, ultrasonically treated with ethanol for 30 minutes, and ultrasonically treated with isopropanol for 30 minutes, it was blown dry with nitrogen, spin-coated with polyvinyl alcohol aqueous solution and rubbed for orientation, a 50 μm PET film was added between two clean glass slides as a spacer layer, and fixed with epoxy resin AB glue to obtain a liquid crystal box;

[0056] 5) Heat the sample to 95°C to present a clear isotropic state, and pour it into the liquid crystal cell using capillary force;

[0057] 6) The liquid crystal box was cooled to BPⅡ (60.0℃), the cooling rate was controlled to 0.2℃ / min, and the temperature was maintained at 60℃ for 60min, and then cooled to BPⅠ (54.0℃), the cooling rate was controlled to 0.01℃ / min, and the temperature was maintained at 54℃ for 120min. The ultraviolet light with a wavelength of 385nm was used at a light intensity of 50mW / cm 2 , irradiation for 120s;

[0058] 7) The liquid crystal box is disassembled to obtain a red blue phase liquid crystal elastomer, the preparation process of which is as follows: Figure 1 The POM photos before and after polymerization, the reflection spectrum, the Kossel pictures after polymerization, and the actual photos of the stretching process are shown in Figure 2 , 3 shown.

[0059] Example 2

[0060] A method for preparing a blue phase liquid crystal elastomer with high thermal stability comprises the following steps:

[0061] 1) Weigh 59.62%, 30%, 3.3%, and 1% of nematic liquid crystal HTG135200-100, liquid crystal polymerizable monomer C6M, chiral compound R5011 with right-handed helical properties, and photoinitiator benzoin dimethyl ether (I-651) according to mass percentage, put them into a 5mL sample bottle, add appropriate amount of dichloromethane to completely dissolve the liquid crystal molecules. Then put the sample bottle into a vacuum drying oven at 40°C overnight to allow the dichloromethane to completely evaporate, and finally obtain a fully and evenly mixed liquid crystal precursor;

[0062] 2) Heat the sample on a hot plate to above the clearing point and use magnetic stirring for more than 30 minutes to ensure that the sample is fully mixed;

[0063] 3) Add 3 μL of catalyst DPA and 6.08% by mass of thiol monomer BDMT at room temperature, and stir magnetically for more than 10 minutes to ensure that the newly added sample is evenly dispersed;

[0064] 4) Preparation of liquid crystal box: After the glass slide was ultrasonically treated with detergent for 30 minutes, rinsed with tap water for 15 minutes, ultrasonically treated with ethanol for 30 minutes, and ultrasonically treated with isopropanol for 30 minutes, it was blown dry with nitrogen, spin-coated with polyvinyl alcohol aqueous solution and rubbed for orientation, a 50 μm PET film was added between two clean glass slides as a spacer layer, and fixed with epoxy resin AB glue to obtain a liquid crystal box;

[0065] 5) Heat the sample to 95°C to present a clear isotropic state, and pour it into the liquid crystal cell using capillary force;

[0066] 6) The liquid crystal box was cooled to BPⅡ (60.0℃), the cooling rate was controlled to 0.2℃ / min, and the temperature was maintained at 60℃ for 60min, and then cooled to BPⅠ (54.0℃), the cooling rate was controlled to 0.01℃ / min, and the temperature was maintained at 54℃ for 120min. The ultraviolet light with a wavelength of 385nm was used at a light intensity of 50mW / cm 2 , irradiation for 120s;

[0067] 7) The liquid crystal box was disassembled to obtain a green blue phase liquid crystal elastomer. The POM and spectrum before and after polymerization were as follows: Figure 2 The actual photo of the stretching process is shown in Figure 3 As shown. Figure 3 It can be seen that the prepared red POM sample has uniform texture, high reflectivity, clear Kossel diffraction characteristic crystal plane and excellent tensile properties.

[0068] Example 3

[0069] A method for preparing a blue phase liquid crystal elastomer with high thermal stability comprises the following steps:

[0070] 1) Weigh 59.22%, 30%, 3.7%, and 1% of nematic liquid crystal HTG135200-100, liquid crystal polymerizable monomer C6M, chiral compound R5011 with right-handed helical properties, and photoinitiator benzoin dimethyl ether (I-651) according to mass percentage, put them into a 5mL sample bottle, add appropriate amount of dichloromethane to completely dissolve the liquid crystal molecules. Then put the sample bottle into a vacuum drying oven at 40°C overnight to allow the dichloromethane to completely evaporate, and finally obtain a fully and evenly mixed liquid crystal precursor;

[0071] 2) Heat the sample on a hot plate to above the clearing point and use magnetic stirring for more than 30 minutes to ensure that the sample is fully mixed;

[0072] 3) Add 3 μL of catalyst DPA and 6.08% by mass of thiol monomer BDMT at room temperature, and stir magnetically for more than 10 minutes to ensure that the newly added sample is evenly dispersed;

[0073] 4) Preparation of liquid crystal box: After the glass slide was ultrasonically treated with detergent for 30 minutes, rinsed with tap water for 15 minutes, ultrasonically treated with ethanol for 30 minutes, and ultrasonically treated with isopropanol for 30 minutes, it was blown dry with nitrogen, spin-coated with polyvinyl alcohol aqueous solution and rubbed for orientation, a 50 μm PET film was added between two clean glass slides as a spacer layer, and fixed with epoxy resin AB glue to obtain a liquid crystal box;

[0074] 5) Heat the sample to 95°C to present a clear isotropic state, and pour it into the liquid crystal cell using capillary force;

[0075] 6) The liquid crystal box was cooled to BPⅡ (60.0℃), the cooling rate was controlled to 0.2℃ / min, and the temperature was maintained at 60℃ for 60min, and then cooled to BPⅠ (54.0℃), the cooling rate was controlled to 0.01℃ / min, and the temperature was maintained at 54℃ for 120min. The ultraviolet light with a wavelength of 385nm was used at a light intensity of 50mW / cm 2 , irradiation for 120s;

[0076] 7) The liquid crystal box was disassembled to obtain a blue blue phase liquid crystal elastomer. The POM and spectrum before and after polymerization were as follows: Figure 2 By comparing the POM and spectra before and after polymerization in Examples 1-3, it can be seen that red, green and blue samples can be obtained respectively by adjusting the ratio of chiral compounds.

[0077] Example 4

[0078] A method for preparing a blue phase liquid crystal elastomer with high thermal stability comprises the following steps:

[0079] 1) Weigh 59.52%, 30%, 3.4%, and 1% of nematic liquid crystal HTG135200-100, liquid crystal polymerizable monomer C6M, chiral compound R5011 with right-handed helical properties, and photoinitiator benzoin dimethyl ether (I-651) according to mass percentage, put them into a 5mL sample bottle, add appropriate amount of dichloromethane to completely dissolve the liquid crystal molecules. Then put the sample bottle into a vacuum drying oven at 40°C overnight to allow the dichloromethane to completely evaporate, and finally obtain a fully and evenly mixed liquid crystal precursor;

[0080] 2) Heat the sample on a hot plate to above the clearing point and use magnetic stirring for more than 30 minutes to ensure that the sample is fully mixed;

[0081] 3) Add 3 μL of catalyst DPA and 6.08% by mass of thiol monomer BDMT at room temperature, and stir magnetically for more than 10 minutes to ensure that the newly added sample is evenly dispersed;

[0082] 4) Preparation of liquid crystal box: After the glass slide was ultrasonically treated with detergent for 30 minutes, rinsed with tap water for 15 minutes, ultrasonically treated with ethanol for 30 minutes, and ultrasonically treated with isopropanol for 30 minutes, it was blown dry with nitrogen, spin-coated with polyvinyl alcohol aqueous solution and rubbed for orientation, a 25 μm PET film was added between two clean glass slides as a spacer layer, and fixed with epoxy resin AB glue to obtain a liquid crystal box;

[0083] 5) Heat the sample to 95°C to present a clear isotropic state, and pour it into the liquid crystal cell using capillary force;

[0084] 6) The liquid crystal box was cooled to BPⅡ (55.0℃), the cooling rate was controlled to 0.2℃ / min, and the temperature was maintained at 55℃ for 60min, and then cooled to BPⅠ (45.0℃), the cooling rate was controlled to 0.01℃ / min, and the temperature was maintained at 45℃ for 120min. The ultraviolet light with a wavelength of 385nm was used at a light intensity of 50mW / cm 2 , irradiation for 120s;

[0085] 7) The liquid crystal box was disassembled to obtain a green blue phase liquid crystal elastomer. Its thermal stability and thermal reversibility were studied by a precision temperature controller. The POM and spectrum changes from -60℃ to 200℃ were as follows: Figure 4 As shown in Figure 2, the temperature is raised from room temperature (23°C) to 150°C and then lowered back to room temperature. The POM and spectrum changes are as follows: Figure 5 As shown. Figure 4 It can be seen that during the entire heating process, the reflectivity remains basically unchanged within the range of 150℃ (-60℃ to 90℃), indicating that the sample has good thermal stability. Figure 5It can be seen that when the sample is cooled to room temperature again, the central wavelength of the reflection peak is consistent with that of the initial sample, and the reflectivity recovers by more than 90%, indicating that the sample has good thermal reversibility.

[0086] Example 5

[0087] A method for preparing a blue phase liquid crystal elastomer with high thermal stability comprises the following steps:

[0088] 1) Weigh 61.04%, 30%, 3.4%, and 1% of nematic liquid crystal HTG135200-100, liquid crystal polymerizable monomer C6M, chiral compound R5011 with right-handed helical properties, and photoinitiator benzoin dimethyl ether (I-651) according to mass percentage, put them into a 5mL sample bottle, add appropriate amount of dichloromethane to completely dissolve the liquid crystal molecules. Then put the sample bottle into a vacuum drying oven at 40°C overnight to allow the dichloromethane to completely evaporate, and finally obtain a fully and evenly mixed liquid crystal precursor;

[0089] 2) Heat the sample on a hot plate to above the clearing point and use magnetic stirring for more than 30 minutes to ensure that the sample is fully mixed;

[0090] 3) Add 3 μL of catalyst DPA and 4.56% by mass of thiol monomer BDMT at room temperature, and stir magnetically for more than 10 minutes to ensure that the newly added sample is evenly dispersed;

[0091] 4) Preparation of liquid crystal box: After the glass slide was ultrasonically treated with detergent for 30 minutes, rinsed with tap water for 15 minutes, ultrasonically treated with ethanol for 30 minutes, and ultrasonically treated with isopropanol for 30 minutes, it was blown dry with nitrogen, spin-coated with polyvinyl alcohol aqueous solution and rubbed for orientation, a 50 μm PET film was added between two clean glass slides as a spacer layer, and fixed with epoxy resin AB glue to obtain a liquid crystal box;

[0092] 5) Heat the sample to 95°C to present a clear isotropic state, and pour it into the liquid crystal cell using capillary force;

[0093] 6) The liquid crystal box was cooled to BPⅡ (55.0℃), the cooling rate was controlled to 0.2℃ / min, and the temperature was maintained at 55℃ for 60min, and then cooled to BPⅠ (48.0℃), the cooling rate was controlled to 0.01℃ / min, and the temperature was maintained at 48℃ for 120min. The ultraviolet light with a wavelength of 385nm was used at a light intensity of 50mW / cm 2 , irradiation for 120s;

[0094] 7) The liquid crystal box was disassembled to obtain a green blue phase liquid crystal elastomer. Its thermal stability was studied by a precision temperature controller. The POM and spectrum changes were as follows when the temperature was raised from 30°C to 200°C. Figure 6 shown.

[0095] Example 6

[0096] A method for preparing a blue phase liquid crystal elastomer with high thermal stability comprises the following steps:

[0097] 1) Weigh 60.28%, 30%, 3.4%, and 1% of nematic liquid crystal HTG135200-100, liquid crystal polymerizable monomer C6M, chiral compound R5011 with right-handed helical properties, and photoinitiator benzoin dimethyl ether (I-651) according to mass percentage, put them into a 5mL sample bottle, add appropriate amount of dichloromethane to completely dissolve the liquid crystal molecules. Then put the sample bottle into a vacuum drying oven at 40°C overnight to allow the dichloromethane to completely evaporate, and finally obtain a fully and evenly mixed liquid crystal precursor;

[0098] 2) Heat the sample on a hot plate to above the clearing point and use magnetic stirring for more than 30 minutes to ensure that the sample is fully mixed;

[0099] 3) Add 3 μL of catalyst DPA and 5.32% by mass of thiol monomer BDMT at room temperature, and stir magnetically for more than 10 minutes to ensure that the newly added sample is evenly dispersed;

[0100] 4) Preparation of liquid crystal box: After the glass slide was ultrasonically treated with detergent for 30 minutes, rinsed with tap water for 15 minutes, ultrasonically treated with ethanol for 30 minutes, and ultrasonically treated with isopropanol for 30 minutes, it was blown dry with nitrogen, spin-coated with polyvinyl alcohol aqueous solution and rubbed for orientation, a 50 μm PET film was added between two clean glass slides as a spacer layer, and fixed with epoxy resin AB glue to obtain a liquid crystal box;

[0101] 5) Heat the sample to 95°C to present a clear isotropic state, and pour it into the liquid crystal cell using capillary force;

[0102] 6) The liquid crystal box was cooled to BPⅡ (55.0℃), the cooling rate was controlled to 0.2℃ / min, and the temperature was maintained at 55℃ for 60min, and then cooled to BPⅠ (46.0℃), the cooling rate was controlled to 0.01℃ / min, and the temperature was maintained at 46℃ for 120min. The ultraviolet light with a wavelength of 385nm was used at a light intensity of 50mW / cm 2 , irradiation for 120s;

[0103] 7) The liquid crystal box was disassembled to obtain a green blue phase liquid crystal elastomer. Its thermal stability was studied by a precision temperature controller. The POM and spectrum changes were as follows when the temperature was raised from 30°C to 200°C. Figure 6 shown.

[0104] Example 7

[0105] A method for preparing a blue phase liquid crystal elastomer with high thermal stability comprises the following steps:

[0106] 1) Weigh 58.76%, 30%, 3.4%, and 1% of nematic liquid crystal HTG135200-100, liquid crystal polymerizable monomer C6M, chiral compound R5011 with right-handed helical properties, and photoinitiator benzoin dimethyl ether (I-651) according to mass percentage, put them into a 5mL sample bottle, add appropriate amount of dichloromethane to completely dissolve the liquid crystal molecules. Then put the sample bottle into a vacuum drying oven at 40°C overnight to allow the dichloromethane to completely evaporate, and finally obtain a fully and evenly mixed liquid crystal precursor;

[0107] 2) Heat the sample on a hot plate to above the clearing point and use magnetic stirring for more than 30 minutes to ensure that the sample is fully mixed;

[0108] 3) Add 3 μL of catalyst DPA and 6.84% by mass of thiol monomer BDMT at room temperature, and stir magnetically for more than 10 minutes to ensure that the newly added sample is evenly dispersed;

[0109] 4) Preparation of liquid crystal box: After the glass slide was ultrasonically treated with detergent for 30 minutes, rinsed with tap water for 15 minutes, ultrasonically treated with ethanol for 30 minutes, and ultrasonically treated with isopropanol for 30 minutes, it was blown dry with nitrogen, spin-coated with polyvinyl alcohol aqueous solution and rubbed for orientation, a 50 μm PET film was added between two clean glass slides as a spacer layer, and fixed with epoxy resin AB glue to obtain a liquid crystal box;

[0110] 5) Heat the sample to 95°C to present a clear isotropic state, and pour it into the liquid crystal cell using capillary force;

[0111] 6) The liquid crystal box was cooled to BPⅡ (50.0℃), the cooling rate was controlled to 0.2℃ / min, and the temperature was maintained at 50℃ for 60min, and then cooled to BPⅠ (45.0℃), the cooling rate was controlled to 0.01℃ / min, and the temperature was maintained at 45℃ for 120min. The ultraviolet light with a wavelength of 385nm was used at a light intensity of 50mW / cm 2 , irradiation for 120s;

[0112] 7) The liquid crystal box was disassembled to obtain a green blue phase liquid crystal elastomer. Its thermal stability was studied by a precision temperature controller. The POM and spectrum changes were as follows when the temperature was raised from 30°C to 200°C. Figure 6 shown.

[0113] Combination Figure 6 It can be seen that in Examples 4 to 7, the thiol content is adjusted, and the central wavelength of the reflection peak of samples with different thiol contents during the heating process generally shows a trend of first redshifting and then blueshifting. In comparison, the sample with C=C:SH of 1:0.8 has a higher reflectivity during the heating process.

[0114] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.

Claims

1. A blue phase liquid crystal elastomer with high thermal stability, characterized in that: The raw materials for preparing the blue phase liquid crystal elastomer include: Nematic liquid crystals, liquid crystal polymerizable monomers, chiral compounds, photoinitiators and thiol monomers; Wherein, the thiol monomer is an aromatic thiol monomer.

2. The blue phase liquid crystal elastomer according to claim 1, characterized in that: The structural formula of the thiol monomer is shown below:

3. The blue phase liquid crystal elastomer according to claim 1 or 2, characterized in that: Calculated by mass percentage, the content of thiol monomer in the raw material is 3-10wt%.

4. The blue phase liquid crystal elastomer according to claim 1, characterized in that: The nematic liquid crystal is selected from one or more of HTG135200-100 and E7; and / or Calculated by mass percentage, the content of nematic liquid crystal in the raw material is 20-80wt%.

5. The blue phase liquid crystal elastomer according to claim 1, characterized in that: The liquid crystal polymerizable monomer is selected from one or more of C6M, C3M, RM257 and C11A; and / or Calculated by mass percentage, the content of liquid crystal polymerizable monomer in the raw material is 10-70wt%.

6. The blue phase liquid crystal elastomer according to claim 1, characterized in that: The chiral compound is selected from one or more of R5011, S5011 and LC756; and / or Calculated by mass percentage, the content of the chiral compound in the raw material is 2.5-4wt%.

7. The blue phase liquid crystal elastomer according to claim 1, characterized in that: The photoinitiator is selected from one of I-651, I-819, I-2959, and I-184; and / or Calculated by mass percentage, the content of the photoinitiator in the raw materials is 0.2-4wt%.

8. The method for preparing a blue phase liquid crystal elastomer according to any one of claims 1 to 7, characterized in that: The steps include: After mixing the nematic liquid crystal, the liquid crystal polymerizable monomer, the chiral compound and the photoinitiator, the thiol monomer is added and mixed to obtain a mixture; After heating the mixture to a clear point of liquid crystal, pouring it into a liquid crystal box; After cooling to BPⅠ, the mixture is polymerized by ultraviolet light to obtain the blue phase liquid crystal elastomer.

9. The preparation method according to claim 8, characterized in that: The cooling is programmed cooling; and / or The cooling method is: Cool down to BPⅡ at a rate of 0.1-5℃ / min and keep warm under this condition; Then cool down to BPI at a rate of 0.01-0.1℃ / min and keep warm under this condition; and / or The conditions of the ultraviolet light polymerization are: The wavelength of the ultraviolet light is 365nm and the light intensity is 50mW / cm 2 , the lighting time is 60-300s.

10. Use of the blue phase liquid crystal elastomer according to any one of claims 1 to 7 in the preparation of stimulus-responsive three-dimensional soft photonic crystal structure materials and sensing, display and anti-counterfeiting devices.